Livin’ Da Dream? Playing Black, Illusions of Meritocracy, and Narrative Constraints in Sports Video Game Story Modes - Michael Fuchs (European Journal of American Studies)
This article discusses sports video game story modes in Fight Night Champion (EA Canada, 2011), a boxing game, NBA 2K16 (Visual Concepts, 2015), a basketball game, and the story that stretches across Madden NFL 18 (EA Tiburon, 2017) and Madden NFL 19 (EA Tiburon, 2018), EA Sports’ annual football series. Focusing on African American athletes, the stories tap into the utopianism of sports and suggest that anyone, irrespective of skin color, can make it in America. This article explores the racial politics of these games, in particular as experienced by a white player such as the author. Primarily focusing on narrative and gameplay, the article discusses how a white player’s control over black bodies confronts them with their racial normativity.